Scale-Up of Capsular Polysaccharide Production Process by Haemophilus influenzae Type b Using kLa Criterion - Pillaca-Pullo, Omar (2022)
Polyribosyl-ribitol-phosphate (PRP) from Haemophilus influenzae type b (Hib) is an active immunizing molecule used in the production of the vaccine against H. influenzae, and industrial production could contribute to satisfying a world demand especially in developing countries. In this sense, the aim of this study was to establish a scale-up process using the constant oxygen mass transfer coefficient (kLa) such as the criterion for production of PRP in three different sizes of bioreactor systems. Three different kLa values (24, 52 and 80 h−1) were evaluated in which the biological influence in a 1.5 L bioreactor and 52 h−1 was selected to scale-up the production process until a 75 L pilot-scale bioreactor was achieved. Finally, the fed-batch phase was started under a dissolved oxygen concentration (pO2) at 30% of the saturation in the 75 L bioreactor to avoid oxygen limitation; the performance of production presented high efficiency (9.0 g/L DCW-dry cell weight and 1.4 g/L PRP) in comparison with previous scale-up studies. The yields, productivity and kinetic behavior were similar in the three-size bioreactor systems in the batch mode indicating that kLa is possible to use for PRP production at large scales. This process operated under two stages and successfully produced DCW and PRP in the pilot scale and could be beneficial for future bioprocess operations that may lead to higher production and less operative cost.